Ethnopharmacological documentation and molecular authentication of medicinal plants used by the Manobo and Mamanwa tribes of Surigao del Sur, Philippines (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ilagan VAD, Alejandro GJD, Paraguison DJB, Perolina SMW, Mendoza GR, Bolina AB, Raterta R, Vales MB, Suarez GJD, Blasco FA. 2022. Ethnopharmacological documentation and molecular authentication of medicinal plants used by the Manobo and Mamanwa tribes of Surigao del Sur, Philippines. Biodiversitas 23: 3185-3202. Mindanao Island is renowned for its rich biodiversity and various ethnolinguistic groups with diverse histories and cultures. The Mamanwa and Manobo live in close proximity, resulting in merging beliefs and cultural practices. This study aims to assess the various medicinal plants using ethnopharmacological indices, determine their relationship to their users, and molecularly confirm unidentifiable plants used by the tribes. Ethnomedicinal data were gathered from 127 key informants representing both tribes through semi-structured interviews. Family Importance Value (FIV) and Use Value (UV) were quantified and revealed a total of 48 species utilized by both tribes belonging to 26 families and 42 genera. These plants are used in 32 diseases within 10 categories, and the most utilized family belongs to Apocynaceae (FIV= 20% for both tribes). Respiratory illness has the greatest contribution to the utilization of medicinal plants (ICF= 0.92, 42%). The most utilized plant part is the leaves and mainly prepared by decoction and administered orally. Integrative molecular confirmation led to the identification of the 5 morphologically unidentifiable plants to be Elaeocarpus serratus Benth., Uncaria lanosa Wall., Aglaonema crispum (J.R. Pitcher & Manda) Nicolson, Canthium tetraphyllum Baill., and Timonous timon (Spreng.) Merr..